Infectious Proctitis in Ulcerative Colitis: The Importance of an Accurate Differential Diagnosis - Saraiva,Miguel Mascarenhas (2021)
Abstract: The authors present the case of a 62-year-old male presenting with a relapse of ulcerative colitis. He had unprotected anal intercourse with other men and his medical record was remarkable for HIV infection. He was admitted to the emergency department with bloody diarrhea, tenesmus, urgency, and recent weight loss. Laboratory workup revealed de novo mild anemia and mild elevation of inflammation parameters. Endoscopic evaluation displayed loss of normal vascular pattern, edema, erythema, exudation, and superficial ulceration in the distal rectum. Biopsies showed chronic proctitis with mild to moderate activity. The patient was treated with intravenous glucocorticoids, but symptoms persisted. Extensive microbial study allowed the identification of multiple infectious agents with potential for infectious proctitis: cytomegalovirus, Chlamydia trachomatis, and Blastocystis hominis. This case highlights the importance of careful microbial investigation, supporting a detailed clinical history, in patients presenting with symptoms of inflammatory bowel disease flare, particularly in risk groups such as that with sexual risk.